IL-11 is a crucial determinant of cardiovascular fibrosis - Schafer,S; Viswanathan,S; Widjaja,AA; Lim,W-W; Moreno-Moral,A; DeLaughter,DM; Ng,B; Patone,G; Chow,K; Khin,E; Tan,J; Chothani,SP; et al. (Nature, 2017)
Fibrosis is a final common pathology in cardiovascular disease1. In the heart, fibrosis causes mechanical and electrical dysfunction1,2 and in the kidney, it predicts the onset of renal failure3. Transforming growth factor β1 (TGFB1) is the principal pro-fibrotic factor4,5 but its inhibition is associated with side effects due to its pleiotropic roles6,7. We hypothesised that downstream effectors of TGFB1 in fibroblasts could be attractive therapeutic targets and lack upstream toxicities. Using integrated imaging-genomics analyses of primary human fibroblasts, we found that Interleukin 11 (IL11) upregulation is the dominant transcriptional response to TGFB1 exposure and required for its profibrotic effect. IL11 and its receptor (IL11RA) are expressed specifically in fibroblasts where they drive non-canonical, ERK-dependent autocrine signalling that is required for fibrogenic protein synthesis. In mice, fibroblast-specific Il11 transgene expression or Il11 injection causes heart and kidney fibrosis and organ failure whereas genetic deletion of Il11ra1 is protective against disease. Thus, inhibition of IL11 prevents fibroblast activation across organs and species in response to a range of important pro-fibrotic stimuli. These data reveal a central role of IL11 in fibrosis and we propose inhibition of IL11 as a new therapeutic strategy to treat fibrotic diseases.